Pemberian Upah Kerja sebagai Pemenuhan Hak Narapidana di Lembaga Pemasyarakatan di Indonesia - Fikri Adiprabowo; Enjum Jumhana; Rahmat Hidayat; Charles Frisheldy Nainggolan (PT. PENERBIT TIGA MUTIARA, 2025)
Inmates in correctional institutions undergo rehabilitation programs that include the development of skills deemed crucial for their lives after being released from prison. Each prisoner is entitled to receive wages or recognition for the efforts they have put into the work they perform. This study focuses on the regulation of rewards for inmates working in correctional facilities, as well as an evaluation of the fairness aspect in their distribution. The study adopts a normative legal analysis approach, utilizing primary legal sources such as laws and government regulations, as well as additional references discussing inmates’ rights in correctional institutions, particularly those related to the payment system for the work they perform. The study finds that the regulations governing inmates’ rights, including those related to wage distribution, are outlined in Article 14 of Law No. 12 of 1995, Government Regulation No. 32 of 1999, and the Minister of Justice Decree No. M.01-PP.02.01 of 1990. From the researcher’s perspective, the distribution of rewards aligns with the principle of fairness because, in addition to receiving rewards, inmates also receive valuable skill training for their future after leaving the correctional institution.